General Anesthesia Does Not Have Persistent Effects on Attention in Rodents - Hambrecht-Wiedbusch, Viviane S.; LaTendresse, Katherine A.; Avidan, Michael S.; Nelson, Amanda G.; Phyle, Margaret; Ajluni, Romi E.; Mashour, George A. (Frontiers in Behavioral Neuroscience, 2019)
Background: Studies in animals have shown that general anesthesia can cause persistent spatial memory impairment, but the influence of anesthetics on other cognitive functions is unclear. This study tested whether exposure to general anesthesia without surgery caused a persistent deficit in attention in rodents. Methods: To evaluate whether anesthesia has persistent effects on attention, rats were randomized to three groups. Group A was exposed for two hours to isoflurane anesthesia, and tested the following seven days for attentional deficits. Group B was used as a control and received room air before attentional testing. Since there is some evidence that a subanesthetic dose of ketamine can improve cognition and reduce disorders of attention after surgery, rats in group C were exposed to isoflurane anesthesia in combination with a ketamine injection before cognitive assessment. Attention was measured in rats using the 5-Choice Serial Reaction Time Task, for which animals were trained to respond with a nose poke on a touchscreen to a brief, unpredictable visual stimulus in one of five possible grid locations to receive a food reward. Attention was analyzed as % accuracy, % omission, and premature responses. Results: Evaluating acute attention by comparing baseline values with data from the day after intervention did not reveal any differences in attentional measurements. No significant differences were seen in % accuracy, % omission, and premature responses for the three groups tested for seven consecutive days. Conclusion: These data in healthy rodents suggest that general anesthesia without surgery has no persistent effect on attention and the addition of ketamine does not alter the outcome.